Synthesis of Volcanic Ash-based Geopolymer Mortar Designed by the Taguchi Method - Rahmi Karolina; Johannes Tarigan; M. A. Megat Johari; M. J. A. Mijarsh; Harianto Hardjasaputra (Civil Engineering Journal, 2022)
This study focuses on the geopolymer synthesized from Mount Sinabung’s volcanic ash. The compressive strength of the geopolymer was determined by optimizing five factors using the Taguchi method’s L16 array. The five factors included: volcanic ash wt.%, Sodium silicate (Na2SiO3) wt.%, Sodium hydroxide (NaOH) concentration (mole), Na2SiO3/NaOH wt.% and water/binder (w/b) wt.%. A total of 16 mixtures were prepared per the L16 array and evaluated on five levels to obtain the optimum mixture. The main findings of this study revealed that A2B1C2D3E4 produced the highest compressive strength of 79.625 MPa after three days of curing time, while A4B2C3D1E4 produced the lowest compressive strength of 41.93 MPa. The signal-to-noise (S/N) ratio analysis from the Taguchi method shows that the factor of Na2SiO3 has a greater impact on compressive strength. The X-ray diffraction (XRD) result for the geopolymer mortar revealed the formation of aluminosilicate type (N-A-S-H) and calcium silicate (C-S-H) gels, whereas the Scanning Electron Microscopy (SEM) result exhibited numerous pores and a denser structure. These characterization results demonstrated that the polymerization of volcanic ash mortar from Sinabung successfully conserves natural resources. Doi: 10.28991/CEJ-2022-08-11-016 Full Text: PDF